2007
DOI: 10.1007/s00198-007-0337-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2 supplementation improves hip bone geometry and bone strength indices in postmenopausal women

Abstract: Summary Vitamin K mediates the synthesis of proteins regulating bone metabolism. We have tested whether high vitamin K 2 intake promotes bone mineral density and bone strength. Results showed that K 2 improved BMC and femoral neck width, but not DXA-BMD. Hence high vitamin K 2 intake may contribute to preventing postmenopausal bone loss. Introduction Vitamin K is involved in the synthesis of several proteins in bone. The importance of K vitamins for optimal bone health has been suggested by populationbased stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
155
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(171 citation statements)
references
References 42 publications
10
155
1
5
Order By: Relevance
“…There are several reports indicating the pharmacological amount of MK-4 supplementation that is beneficial for OC carboxylation in healthy aged people (11,12) as well as in osteoporotic postmenopausal women (21). However, in case of insufficient daily intake of vitamin K for bone metabolism, the exact amount of MK-4 supplementation required to accelerate the carboxylation of OC in healthy postmenopausal women is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports indicating the pharmacological amount of MK-4 supplementation that is beneficial for OC carboxylation in healthy aged people (11,12) as well as in osteoporotic postmenopausal women (21). However, in case of insufficient daily intake of vitamin K for bone metabolism, the exact amount of MK-4 supplementation required to accelerate the carboxylation of OC in healthy postmenopausal women is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adults, about 30 % of circulating OC is undercarboxylated [10,11]. Increased vitamin K intake causes a rapid decline in undercarboxylated OC (ucOC) [8,12], suggesting possible subclinical vitamin K deficiency in "healthy" bone tissue [4].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study confirmed the beneficial effect of vitamin K1 supplementation on BMD in postmenopausal women, with doses of 80mcg/d phylloquinone proving effective 66 . There were, however, mixed results for MK4, with one trial showing that 45mg/d, together with vitamin D and calcium, had a beneficial effect on BMD in Korean postmenopausal women 71 , while another showed that MK4 enhanced the effect of bisphosphonates in Japanese postmenopausal females 72 but a larger study over three years found no effect on BMD, although BMC and femoral neck width were increased compared to placebo 73 . 180mcg/d MK7 also significantly improved BMD in postmenopausal women 74 , although 360mcg/d MK7 failed to show a difference in bone loss relative to the placebo group 75 but this may have been because the placebo was olive oil, which also has a beneficial effect on bone 3 .…”
Section: Bonementioning
confidence: 99%